Serabit el-Khadem, Southeastern Sinai: Getting to Know an Ancient Egyptian Mining Site Through its Ceramics - Caelen, Veerle; Degryse , Patrick (Antiguo Oriente, 2025)
When the results of the work carried out by the expeditions to Serabit el-Khadem by Flinders Petrie, Richard Starr and Dominique Valbelle and Charles Bonnet are observed, it immediately becomes clear that the epigraphic, iconographic and architectural remains at Serabit have received a lot of attention. More mundane objects such as ceramics, faience and lithics have seen less consideration. Despite this inattention, these materials can still tell us much about the organization of the mining expeditions, the site of Serabit el-Khadem, and about their dependence on the Egyptian mainland. Moreover, the study of these objects might gain even more importance since new archaeological research at Serabit is hampered by the erosion and weathering of the inscribed stelae and architectural remains caused by both human and natural factors. Except for a short macroscopic study of ceramics gathered in the 1990s under direction of Bonnet and Valbelle, no pottery from Serabit el-Khadem was studied in detail. The sherds studied here come from Starr’s expedition in 1935 and is currently stored at the Harvard Museum of the Ancient Near East in Massachusetts. This study intends to fill the void of material studies at Serabit el-Khadem by performing macroscopic and microscopic (thin-section) analyses of Starr’s pottery sherd collection from the temple area. The main goal of this study is to revisit this old museum collection in order to try and gain new information on Serabit el-Khadem and its mining expeditions.